Perbedaan Ketebalan Anatomi Daun Enam Jenis Tanaman Hias Monokotil pada Posisi Pangkal dan Pucuk - Minati; Entin Daningsih; Asriah Nurdini Mardiyyaningsih (Postgraduate, University of Mataram, 2023)
The position of the leaves on each plant can affect the thickness of the leaf tissue. This study aims to determine the thickness of the leaf tissue at the base and shoot positions. The study used a nested design model (random nesting pattern design). This design uses two factors, the first factor is the leaves of six types of monocot ornamental plants, namely adam hawa (Rhoeo discolor), daffodils (Hymenocallis littoralis), hanjuang (Cordyline fructicosa), lilies of paris (Chlorophytum laxum), song india (Dracaena reflexa) and sri fortune (Aglaonema commutatum), while the second factor was leaf position (base and shoot) with three replications. The method of making leaf preserved preparations is paraffin which refers to Johansen. Parameters measured were total leaf thickness, upper epidermis, lower epidermis, mesophyll (palisade and sponge). Data were analyzed with ANOVA followed by LSD if the factor results were significant. The correlation was made between the total leaf thickness and the tissue which was significant on the leaf position factor. The results showed that the type of plant affected the total leaf thickness, upper and lower epidermis, mesophyll (palisade and sponge). However, leaf position has no effect on the thickness of the upper epidermis and sponge for differentiated mesophyll. The thickness of the leaf depends on the thickness of the lower epidermis, followed by the thickness of the mesophyll or palisade for differentiated mesophyll.